Answer:
me
Step-by-step explanation:
Get the x variable on one side and the numbers another side.
9/10(x + 2/3) = 4 1/2
Distribute the 9/10 across the x and 2/3.
(9/10)x + 18/30 = 4 1/2
Simplify 18/30 to make our life easier.
(9/10)x + 3/5 = 4 1/2
Subtract 3/5 from each side of the equation.
(9/10)x = 3 9/10
Divide both sides by 9/10.
x = 4 1/3
Answer:
57/26 or 2 5/26
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
Sum the product of the components in the first row of A with the corresponding components of the first column in B
Repeat this with the components in the second row of A with the corresponding components of the second column in B, that is
AB
=
![\left[\begin{array}{ccc}3&1\\5&2\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%261%5C%5C5%262%5C%5C%5Cend%7Barray%7D%5Cright%5D)
= ![\left[\begin{array}{ccc}2(3)+1(5)&2(1)+1(2)\\3(3)+4(5)&3(1)+4(2)\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%283%29%2B1%285%29%262%281%29%2B1%282%29%5C%5C3%283%29%2B4%285%29%263%281%29%2B4%282%29%5C%5C%5Cend%7Barray%7D%5Cright%5D)
= ![\left[\begin{array}{ccc}6+5&2+2\\9+20&3+8\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D6%2B5%262%2B2%5C%5C9%2B20%263%2B8%5C%5C%5Cend%7Barray%7D%5Cright%5D)
=
→ A
<span>your answer is (5 + t)(-5 + t)</span>